Advanced healthcare materials - Tiwari, Ashutosh, 1978- (Beverly, MA : Scrivener Publishing ; Hoboken, New Jersey : Wiley, 2014)
"Advanced materials are attracting strong interest in the fundamental as well as applied sciences and are being extensively explored for their potential usage in a range of healthcare technological and biological applications. Advanced Healthcare Nanomaterials summarises the current status of knowledge in the fields of advanced materials for functional therapeutics, point-of-care diagnostics, translational materials, up and coming bio-engineering devices. The book highlights the key features which enable engineers to design stimuli-responsive smart nanoparticles, novel biomaterials, nano/micro-devices for diagnosis, therapy (theranostics).The leading contributor researchers cover the following topics: State-of-the-art of biomaterials for human health Micro- and nanoparticles and their application in biosensors The role of immunoassays Stimuli-responsive smart nanoparticles Diagnosis and treatment of cancer Advanced materials for biomedical application and drug delivery Nanoparticles for diagnosis and/or treatment of Alzheimers disease Hierarchical modelling of elastic behavior of human dental tissue Biodegradable porous hydrogels Hydrogels in tissue engineering, drug delivery and wound care Modified natural zeolites Supramolecular hydrogels based on cyclodextrin poly(pseudo)rotaxane Polyhydroxyalkanoate-based biomaterials Biomimetic molecularly imprinted polymers The book is written for readers from diverse backgrounds across chemistry, physics, materials science and engineering, medical science, pharmacy, biotechnology, and biomedical engineering. It offers a comprehensive view of cutting-edge research on advanced materials for healthcare technology and applications"--
"Advanced Healthcare Nanomaterials summarises the current status of knowledge in the fields of advanced materials for functional therapeutics, point-of-care diagnostics, translational materials, up and coming bio-engineering devices"--
Functional therapeutics -- Point-of-care diagnostics -- Translational materials -- Emerging bio-engineering devices.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Nanotechnology -- Health aspects; Nanomedicine; TECHNOLOGY & ENGINEERING / Material Science; Electronic books